Ultrasound Examination of the Pupil – A New Tool for the Neuro-Ophthalmological Assessment - Farina, Filippo; Vosko, Milan R.; Baracchini, Claudio; Ermani, Mario; Sommer, Peter; Greisenegger, Stefan; Laubichler, Peter; Struhal, Walter; Kellermair, Lukas; Ransmayr, Gerhard; Brunner, Cornelia (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Background Pupil examination represents a diagnostic and prognostic test in the management of several neurological diseases. Infrared video pupillometry (IVP) is the gold standard, since it is not routinely available, a noninvasive bedside ultrasound assessment has been proposed as an alternative. The aim of this study was to assess the feasibility and reproducibility of ultrasound pupillometry (UP) in comparison with IVP.Materials and Methods 81 subjects (43 men and 38 women, mean age: 52 ± 20 years and 49 ± 19 years, respectively) with no history of neurophthalmologic disease were enrolled. UP was performed with a 12-MHz linear probe according to current guidelines for orbital insonation. Light and painful stimuli were applied to test pupillary light reflex (PLR) and ciliospinal reflex (CR). In 30 of these subjects IVP examination was performed additionally to obtain intra-observer and inter-observer agreement.Results Increasing age was associated with a decreased pupillary diameter (PD) at rest, after PLR and CR (R –0.728, p < 0.01, R –0.643, p < 0.01, R 0.674, p < 0.001 respectively), while no association was noticed with time to constriction/dilation. UP measurements were reproducible (rate of inter- and intra-observer agreement: R 0.979, p < 0.01, R 0.946, p < 0.01 respectively) and concordant with IVP (PLR R 0.831, p < 0.01; CR R 0.879, p < 0.01).Conclusion According to our study, ultrasound pupillometry is a feasible and reliable technique for bedside pupillary function assessment, and is a good alternative to infrared video pupillometry. Moreover, it represents the only way for functional pupillary assessment in patients with periorbital hematoma.
Keywords: ultrasound; pupil; pupillary light reflex; ciliospinal reflex; video pupillometry